A highly selective fluorescent sensor for Cu2+ based on naphthalimide containing aza‐crown ether. (11th December 2021) - Jeon, Sumin; Lee, Seongman; Choi, Yeonghwan; Kim, Mi‐Ra; Lee, Songyi
Abstract: The development of a fluorogenic chemosensors with high sensitivity for copper ion (Cu 2+ ) has been receiving great attention in recent years because of their potential application in clinical biochemistry and the environment studies. In the present study, we designed and synthesized a fluorescent probe, Np‐azaCE, with 1, 8‐naphthalimides as a core structure and 1, 4‐diaza‐9‐crown‐3‐ether as a copper ion tweeze, which showed selective and sensitive fluorometric change upon addition of a copper ion. The Np‐azaCE chemosensor was highly selective for Cu 2+ over the other metal ions with fluorescent quenching. Finally, the Cu 2+ detection limit and job's plot of Np‐azaCE were calculated using UV–visible spectrophotometer and fluorescence spectrophotometer. Abstract : This article describes the preparation and analysis of Cu 2+ ‐sensing naphthalimide‐based chemosensors (Np‐azaCE ).